From the history of the formation of the Dubrovnik intelligentsia. Representatives, institutions, and forms of activity in the first half of the 19th century - Kubik, Damian (Poznańskie Studia Slawistyczne, 2024)
The article presents the most important phenomena related to the intellectual activity of Dubrovnik elites on the cultural level in the first half of the 19th century. The starting point of the text is the socio-class and religious image of Dubrovnik which allows for discussion of the intellectual atmosphere and its impact on cultural life in the city. An important part of the present analyses are also issues related to initiatives integrating Dubrovnik’s intelligentsia, as well as the importance of the 1830s and 1840s (with particular emphasis on 1848) for the changes taking place in the life of the city. The summary of the article emphasizes that Dubrovnik’s loss of independence did not mean the end of its rich tradition, but also enabled the formation of circles that played an important role in the Croatian national revival.